2021
DOI: 10.1021/acsestengg.1c00156
|View full text |Cite
|
Sign up to set email alerts
|

Disordered MoS2 Nanosheets with Widened Interlayer Spacing for Elemental Mercury Adsorption from Nonferrous Smelting Flue Gas

Abstract: The development of a sorbent with a large elemental mercury (Hg0) adsorption capacity under a high SO2 concentration atmosphere is the key point for mercury emission control from nonferrous smelting (NFS) flue gas. By controlling the degree of crystallization, oxygen incorporation and disorder engineering were simultaneously realized to improve the Hg0 adsorption capacity of MoS2 nanosheets for the first time. The interlayer spacing of oxygen-incorporated MoS2 nanosheets reaches up to 9.4 Å from 6.4 Å of norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The presence of surface vacancies can generally improve the Hg 0 adsorption performance of metal sulfides through reducing the saturation of active sites . For example, the Hg 0 removal efficiency of N–MoS 2 with surface defects was significantly better than that of B–MoS 2 , and DFT calculations suggested that the formation of S vacancy increased the positive potential of the MoS 2 (001) surface, which facilitated the capture of Hg valence electrons. , On the basis of the defect formation energy, the type of formed vacancies over metal sulfides can be determined. The formation of S vacancy can reduce the saturation of adjacent M sites, thereby facilitating the Hg 0 pre-adsorption process at low adsorption temperature .…”
Section: Engineered Metal Sulfidesmentioning
confidence: 99%
“…The presence of surface vacancies can generally improve the Hg 0 adsorption performance of metal sulfides through reducing the saturation of active sites . For example, the Hg 0 removal efficiency of N–MoS 2 with surface defects was significantly better than that of B–MoS 2 , and DFT calculations suggested that the formation of S vacancy increased the positive potential of the MoS 2 (001) surface, which facilitated the capture of Hg valence electrons. , On the basis of the defect formation energy, the type of formed vacancies over metal sulfides can be determined. The formation of S vacancy can reduce the saturation of adjacent M sites, thereby facilitating the Hg 0 pre-adsorption process at low adsorption temperature .…”
Section: Engineered Metal Sulfidesmentioning
confidence: 99%
“…6(a) & (b)). Both SO 2 and H 2 O slightly inhibited Hg 0 adsorption on pristine ZnS, probably because of competition for active sites among Hg 0 , SO 2 , and H 2 O 12,16,22 and/or coverage of active sites by the highly concentrated H 2 O 15,37 . O 2 gas is a highly enriched component in industrial flue gases, but it exhibits a negligible influence on Hg 0 adsorption by metal sulfides 10,15,[38][39][40] , so it was not studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…32 To enhance the exposure of the vast sulfur atoms on the basal plane, an oxygen insertion method has been developed previously to enlarge the interlayer spacing of MoS 2 . 33 However, due to the small volume of inserted oxygen atoms, this method cannot improve the thermal stability of MoS 2 . In this aspect, foreign molecule insertion provides a promising candidate because the larger volume of inserted molecules will be more helpful to prevent the structure collapse of MoS 2 nanosheets at a high temperature.…”
Section: Introductionmentioning
confidence: 99%